Solvent Free Synthesis of Trialkylammonium Chromates (TAC) as Oxidative Promoter (SNPRC Journal, 2024)
Trialkylammonium halochromates (R3NH[CrO3X]) (R = C2H5, C4H9, C3H7, CH3; X = F, Cl) are a beneficial addition to the oxidant series because of their affordability, availability, and effectiveness in oxidizing a wide range of organic compounds. A gentle and effective technique that uses trialkyl ammonium fluorochromates at room temperature and microwave radiation to oxidize diols to hydroxyl aldehydes offers a rapid, selective, and environmentally friendly approach, minimizing by-product formation and preserving sensitive functional groups during the oxidation process Traditional chromium-based oxidants frequently have problems such as poor selectivity, unfavorable reaction conditions, and hazardous byproducts that pose a threat to the environment. By exploring trialkylammonium chromates and halochromates, this study aims to overcome these challenges by identifying more effective and potentially greener alternatives for the oxidation of vanillin, while also examining how different halide ions influence the reaction outcome. The goal of the study is to comprehend how halide changes impact vanillin oxidation and aid in the creation of more potent and selective oxidants based on chromium. Our findings revealed that the nature of the halide significantly influenced the oxidation rate and product yield, with bromochromate showing higher reactivity. This study contributes to understanding the role of halide ligands in chromium (VI) oxidations and supports the development of more selective oxidants for aromatic compounds like vanillin.